Resistir através da rede: análise netnográfica do movimento #adiaENEM no Norte do Brasil - BARBOSA, Ana Karoline (Universidade Federal do Pará, 2022)
The coronavirus pandemic deeply changed people relationships and routines around the world. The impossibility of going out and meet friends and family through social distancing and self-quarantine, recommended by principal sanitary authorities, has been causing deeply impacts and consequences still impossible to be concluded. At this pandemic period, many sectors have been affected, as social distancing was required through the whole world. A particular event, which is this research main object, has gained broad debate not just on media, but also on online social media: the Brazilian High School National Exam (ENEM) application. Came about, then, the online social movement #adiaENEM, whose objective was to postpone the exam application that was scheduled to November 2020 and got transferred to January 2021. Given this context, the main objective of this study is to analyze the online social movement #adiaENEM on Twitter during COVID-19 pandemic period. This research proposes reflection about the pandemic and online manifestation through twitter social media, about the test postpone on northern region of Brazil. This study theoretical basis is on the understanding of online social movements (CASTELLS. RECUERO) and power relations (FOUCAULT. SCOTT) constructed through inequalities, daily resistance, transversal struggles, and the subject autonomy (MIGUEL). Proposing a methodological approach by netnography (KOZINETS) arranged in two moments, a content analysis and a network analysis. To analyze the speech content (BARDIN) produced by the social movement the software IRAMUTEQ has been used, allowing the investigation through the tweet corpus that mentioned the northern region, your states, and capitals. Five types of analysis were carried out (lexicographical, factorial correspondence, hierarchical descending classification, similarity, and word cloud). The network analysis (RECUERO) was carried out by graph analytics generated by VOSviewer, seeking to list the main stakeholders mentioned on #adiaENEM national movement. After those analyses a comparative study was executed (FACHIN) between the two movement moments in May 2020 and January 2021. It was concluded then, that the two tides of the movement differ on argumentation and network structure, as the central point of 2020 tide was the social and structure inequalities between the applicants, and in 2021 the central point was the coronavirus pandemic, and the health risk with the exam application.